Advertising modern art: a semiotic analysis of posters used to communicate about the Turner Prize award. (November 2015) - Sifaki, Eirini; Papadopoulou, Mary
This article probes into the visual discourse expressed in a selection of advertising posters designed to promote the 'Turner Prize', a contemporary art award organized by the Tate Gallery in London. Four posters were chosen from 1994 to 2011, a 17-year period in the history of the prize that was marked by controversial candidate choices, polarizing critical reviews by art critics in the media and the seemingly deliberate fostering of an audience comprised of ardent fans and detractors. Through a semiotic deconstruction of the visual images and textual messages employed, with an emphasis placed on their multidimensional structure and its intersection with the social context of viewing, this article provides a critical analysis of the role played by visual design of the posters' potential for boosting audience development and the effectiveness of the communication strategies put in place by the Gallery. The analysis reveals that the posters' effectiveness on specific target groups cannot be overshadowed by more up-to-date means of communication. Nevertheless, the Tate's persistence in focusing on media attention as an advertising practice leaves other aspects of the institution's identity unexplored.